2014
DOI: 10.1371/journal.pone.0102555
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations in the Brain Associated with HIV-1 Infection and Methamphetamine Dependence

Abstract: HIV involvement of the CNS continues to be a significant problem despite successful use of combination antiretroviral therapy (cART). Drugs of abuse can act in concert with HIV proteins to damage glia and neurons, worsening the neurotoxicity caused by HIV alone. Methamphetamine (METH) is a highly addictive psychostimulant drug, abuse of which has reached epidemic proportions and is associated with high-risk sexual behavior, increased HIV transmission, and development of drug resistance. HIV infection and METH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…One global methylation study found decreased DNAm in the blood of alcohol drinkers (Alu, not LINE-1 [39]). Results contrast those of increased global methylation identified in the frontal cortex of HIV+ methamphetamine users versus non users [40], as well as in the blood of methadone-substituted former opiate addicts, an effect which was also replicated in independent sample of opioid-treated patients [41]. Candidate gene studies focused mainly on genes involved in neural function, most likely guided by existing neurochemical data regarding addiction on animals and humans.…”
Section: Adulthoodmentioning
confidence: 97%
See 1 more Smart Citation
“…One global methylation study found decreased DNAm in the blood of alcohol drinkers (Alu, not LINE-1 [39]). Results contrast those of increased global methylation identified in the frontal cortex of HIV+ methamphetamine users versus non users [40], as well as in the blood of methadone-substituted former opiate addicts, an effect which was also replicated in independent sample of opioid-treated patients [41]. Candidate gene studies focused mainly on genes involved in neural function, most likely guided by existing neurochemical data regarding addiction on animals and humans.…”
Section: Adulthoodmentioning
confidence: 97%
“…Hypomethylation was also observed in long terminal repeat (LTR) regions of retrotransposons in the superior frontal cortex of postmortem alcohol users [56]. Other important pathways related to apoptosis [52,54,55], metabolism [53], as well as GABA and dopamine systems [40,53].…”
Section: Adulthoodmentioning
confidence: 98%
“…Most of our understanding of deep HIV reservoirs has come from autopsy studies, but these previous studies had variable ART intake and limited ante-mortem characterization that can be compared to post-mortem measures [12, 30, 31]. Also, there is typically a significant delay in time from ante-mortem visits until death (for example the average time between the last clinical assessment and death is 262.6 days (Standard deviation: 402.7 days) and is rarely < 6 months in the California NeuroAIDS Tissue Network [32]).…”
Section: Opinion Piecementioning
confidence: 99%
“…Recent studies using postmortem HIV-infected brains have addressed nuclear DNA methylation, mitochondrial DNA injury, and cerebral gliosis (Desplats et al 2014; Soontornniyomkij et al 2016; Var et al 2016). Epigenetic changes were investigated in the frontal cortex of HIV-infected individuals with or without Meth dependence (Desplats et al 2014).…”
Section: Neuropathologymentioning
confidence: 99%
“…Epigenetic changes were investigated in the frontal cortex of HIV-infected individuals with or without Meth dependence (Desplats et al 2014). Meth was associated with increased expression levels of DNMT1 gene (DNA (cytosine-5)-methyltransferase-1 enzyme involved in the maintenance of DNA methylation) and increased levels of global DNA methylation that correlated directly with HIV-1 RNA levels.…”
Section: Neuropathologymentioning
confidence: 99%